POTENTIAL OF AGRICULTURAL PRODUCTION AND ITS IMPACT ON INSURANCE PREMIUMS - Birovljev, Jelena; Vojinović, Željko; Balaban, Mladenka (Economics of Agriculture, 2015)
Food production is becoming very important and it receives priority in relation to other activities in the world. As the number of inhabitants of the planet grows, food production has greater signifcance. Its production will certainly be affected by climate changes and the potential of agricultural land, which will be followed by changes in insurance cover of crops. Total area of arable land doesnt have the same quality, but its especially common for underdeveloped and developing countries is that arable land is not used in the appropriate percent. For Serbia which belongs to that group of countries with low yield on arable land, it can be pointed out that insurance does not cover a suffcient share of that area. The reason for this lies in the lack of trust of potential insured, habits and consciousness of the insured, economic policy pursued by the state in relation to this issue, inadequate training of insurance agents and the lack of proper insurance products.